KONSTRUK DISONANSI KOGNITIF DALAM PENELITIAN PERILAKU KONSUMEN: APAKAH POPULARITASNYA MEMANG SUDAH MEREDUP? - Alfitman Alfitman (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Malang, 2017)
Abstract: This article explains whether the constructs of cognitive dissonance have dimmed or have not been used in consumer behavior research. This issue comes with the emergence of several studies that no longer include this construct in their research. Based on literature studies in the top journals of marketing, the findings suggest that cognitive dissonance constructs are still popular and widely used in marketing research. These findings are important for academic and practical development purposes, as these constructs are useful for supporting the implementation of marketing strategies especially for marketers who apply the concept of